Grumixama extract as natural additive on fermented sausage to control lipid oxidation - Ojoli, Gabriela Xavier [UNESP]; Mangueira, Rick Anderson Freire [UNESP]; Junior, Carlos Alberto Alves [UNESP]; Bertuci, Marcello Lima [UNESP]; da Silva Barretto, Andrea Carla [UNESP] (Elsevier, 2025)
Purple grumixama (Eugenia brasiliensis) is a native fruit of the Brazilian Atlantic Forest with an intense purple coloration, belonging to the Myrtaceae family. This study evaluated the antioxidant effects of purple grumixama extract (GE) on the lipid stability in fermented sausage. Five treatments were prepared in fermented sausage: CON (without antioxidant), ERY (500 mg.kg-1 of sodium erythorbate), and grumixama extract at three levels - GE500 (500 mg.kg-1), GE1000 (1000 mg.kg-1), and GE1500 (1500 mg.kg-1). This study aimed to evaluate the physicochemical, antimicrobial, textural, and sensory attributes of fermented sausage during its ripening time. At the lowest concentration, GE showed lower thiobarbituric acid reactive substances (TBARS) values on day 1 (GE500). On day 14, the TBARS values for the control (CON) were above 0.5 MDA kg-1, whereas all treatments with GE were close to 0.3 MDA kg-1. Although the instrumental texture parameters were higher for the fermented sausage with GE, especially at the higher concentrations, frequent consumers of fermented sausage did not notice any difference. Fermented sausages are generally characterized by a low pH, reduced water activity, a firm texture, a characteristic reddish color, and a complex flavor. Parameters such as approximate composition, instrumental color, pH, weight loss, and lactic acid bacteria count were not altered, maintaining typical characteristics of the fermented sausage. The addition of GE is a promising natural additive to replace synthetic antioxidants, as it improves oxidative stability without altering the traditional desirable parameters in fermented sausage.